The estimation of the stability of the characterization of the exponential distribution - Nhu, Hoang huu (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Хоанг Хыу Ньы. Оценка устойчивости одной характеризации экспоненциального закона Hoang huu Nhu. Vieno eksponentinio dėsnio charakterizacijos stabilumo įvertinimas